Prognostic role of the Rockwood Clinical Frailty Scale in patients with acute heart failure:results from a single-centre retrospective cohort study. (26th April 2021) - Todd, F; Wong, C; Hewitson, L; Mohamed, A; Doolub, J; Gogola, L; Skyrme-Jones, A; Aziz, S; Sammut, E; Dastidar, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Acute decompensated heart failure carries a poor prognosis and places a significant burden on healthcare resources. Our ability to predict patients at high risk of deterioration is limited. The Rockwood Clinical Frailty Scale (CFS) is an established frailty screening tool that stratifies patients on a nine-point scale ranging from 1 (very well) to 9 (terminally ill) providing a useful measure of physiological reserve. CFS is used extensively for general prognostication in geriatric populations, yet its impact on mortality specifically in patients admitted with acute heart failure remains sparsely investigated. Purpose: We performed a retrospective cohort study to investigate the prognostic role for CFS for short term mortality in patients admitted with acute heart failure. Methods: Over a period of 16 weeks (7th January – 27th April 2020), 283 consecutive patients presenting to our hospital with signs and symptoms of acute heart failure were identified. Discharge summaries, electronic notes and shared care networks were manually searched for each patient to determine frailty score, baseline demographics, admission bloods and co-morbidity indices. Short term mortality at 30 days was recorded from electronic hospital and GP records. Univariate and multivariate Cox regression analysis was performed to identify clinical and biochemical predictors of mortality. Results: In total, 283 patients were admitted with acute heart failure over the study period (mean age 81+/-10 years, 46% female. The mean CFS score was 5+/-1 and mean Charlson Comorbidity Index score 8+/-3. 15% of patients died within 30 days. On univariate analysis age, creatinine, Charlson Comorbidity Index and CFS were associated with prognosis. On multivariate analysis, only CFS was found to be an independent predictor of mortality (hazard ratio 1.36, p = 0.029). Conclusion: This study demonstrates a clear relationship between increasing frailty score and short-term mortality in acute heart failure. The CFS is a rapid and easily accessible screening tool used widely throughout the UK. This work highlights its potential for use alongside other parameters in prognostication of patients presenting with acute decompensated heart failure. Further work is needed to explore the impact on longer term mortality and to determine practical implementation in this setting.